Workforce Diversity and Employee Performance in the Local Government of Kanchanpur, Nepal - Saud, Dhan Bahadur (Journal of Business and Management, 2023)
Background: In today’s highly competitive governance, diversity has become one of the most critical executive issues, as the local governments have increasingly become diverse concerning their workforce. Diversity emerges in a local government when its members differ from one another. The concept of diversity includes recognizing, accepting, and respecting each difference and understanding that each is unique. Objectives: The main objective of this paper is to investigate the association between employee performance and workforce diversity in the local government of Kanchanpur district. Methods: The study adopted a descriptive research design. Purposive and cluster sampling techniques were used, and a structured questionnaire was used to collect the data from 400 employees of different municipalities of Kanchanpur district. To analyze data correlation matrices, ANOVA tables, and coefficient tables as outputs of regression. Results: The employees in the local governments are becoming more diverse because of the political reforms, the global practice of local government, competitiveness and change in customer preferences, and inclusive participation in the constitution. With the drastic change in politics, the formation of the progressive constitution of Nepal increasing reforms in the last two decades and changing demographics of the labour market local government has become a place for diversity inclusion. Conclusion: The result revealed that ethnicity diversity, educational diversity, and work performance diversity have positive impacts on employees’ performance. Further, physical disability has a negative impact on employees’ performance. This study highlights how workforce diversity affects employees’ performance in the local governments of Kanchanpur district. These results can be used to build strategies to improve the implementation of employee diversity in existing local governments.